Relationship of Intrapersonal and Interpersonal Intelligence with Teamwork and Performance of Karate Athletes - Nuraeni, Alfi; Komarudin, Komarudin; Mulyana, Mulyana (UNIVERSITAS NEGERI MAKASSAR, 2021)
The components of intrapersonal and interpersonal intelligence have been widely studied in the psychological domain of emotional intelligence. Intrapersonal intelligence is closely related to the individual's ability to recognize, regulate, and express one's feelings and emotions. The purpose of this study was to examine the relationship between intrapersonal and interpersonal intelligence with teamwork and the performance of athletes in the sport of karate. This research method is descriptive quantitative with a correlational research design. The population of this research is the beginner karate athletes in the said team number in Cianjur Regency with a total of 21 athletes. With characteristics: (1) Team kata karate athletes in Cianjur Regency who have received an intensive training program, (2) Age level is between 12-16 years, (3) Has practiced karate for at least 1 year, (4) Minimum belt level is yellow. The sampling technique in this study uses total sampling. The conclusion of this study shows that intrapersonal intelligence and interpersonal intelligence have a significant influence on teamwork for team kata athletes in karate sports, teamwork team kata athletes karate can be explained or influenced by variables of intrapersonal intelligence and interpersonal intelligence by 24.9%, while 75.1% is influenced by variables that are not studied, intrapersonal and interpersonal intelligence do not have a significant influence on the performance of team athletes in karate, the performance of team athletes in karate is influenced by variables of intrapersonal intelligence and interpersonal intelligence of 0.56 %, while the remaining 99.44% is influenced by variables not examined.